Developing a teacher agent to explore the role of gaze direction on young school children’s comprehension - Brännström, Jonas; Waechter, Sebastian; Nirme, Jens; Whitling, Susanna; Lyberg-Åhlander, Viveka; Sahlén, Birgitta (Acta Logopaedica, 2024)
Teachers’ gaze and school children’s language proficiency play a role for listening comprehension in the classroom. The influence of multimodal conditions on listening comprehension may be hard to study in a systematic manner with real speakers. The aim was to test the concept and feasibility of studying the influence of a speakers on passage comprehension performance in children using a digitally animated character. Twenty-four primary-school children were tested. A narrative passage was presented to the participants by a teacher agent. Half of the participants were randomized to a direct gaze condition and half to an averted gaze condition. The method is feasible with the intended population. We detected no differences in listening comprehension of the teacher agent’s gaze behavior in our sample. The concept works and it is feasible to test the effect of speaker gaze on children using the proposed methodology with some further development. Abstract på svenska Lärarnas blickbeteende och skolbarns språkkunskaper spelar roll för hörförståelsen i klassrummet. Inverkan av multimodala förhållanden på hörförståelse kan vara svår att studera på ett systematiskt sätt med riktiga talare. Syftet med denna studie var att utveckla en metod för att studera en talares inflytande på förståelse av textpassager med hjälp av en digitalt animerad karaktär. Tjugofyra grundskolebarn testades. En passage ur en berättelse presenterades för deltagarna av en animerad lärarfigur. Hälften av deltagarna randomiserades till ett direkt blickstillstånd och den andra hälften till ett bortvänt blickstillstånd. Metoden kunde användas med den avsedda populationen, men vi upptäckte inga skillnader i hörförståelse på grund av blickbeteende i vårt urval. Metoden behöver vidareutvecklas, såsom ett dynamiskt blickbeteende för den animerade lärarfiguren innan den kan användas för att visa hur blickbeteendet påverkar barns hörförståelse. Den svenska versionen av abstractet lades till i version 2 av denna artikel. Översättningen gjordes av tidskriftens redaktion.